Growth Dynamics And Resource Allocation Of Bistorta Amplexicaulis (D. Don) Greene: An Alteration Across Different Habitats And Altitudes - Javid, Hanan; Roof Ul Qadir; Magray, Junaid A.; Wani, Bilal A.; Irshad A. Nawchoo; Shabana Gulzar (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Bistorta amplexicaulis is an essential medicinal plant found in the Kashmir Himalaya. Ethnobotanical studies have revealed that this particular species is used to treat fractures, muscle injuries, heart problems, abnormal leucorrhoea, menorrhagia and inflammation of the mouth and tongue. The current study aimed to determine the variation in growth traits and fluctuations in the allocation patterns with respect to different habitats across the altitudinal gradient. In order to adapt to unpredictable and stressful conditions at higher altitudes, phenotypic plasticity plays a crucial role. Our findings revealed considerable variability in the phenotypic traits, indicating that altitude has a defined effect on this specific species’s morphology and reproductive traits. Low altitude plant populations of Kashmir University Botanical Garden (KUBG), Dara and Tangmarg were more robust and taller (98.4±2.36, 83.58±2.69 and 74.08±1.59 cm, respectively) than the populations of Pissu top and Bangus (23.96±3.38 and 30.43±1.12 cm respectively) at higher altitudes. The habitats of KUBG, Dara, and Tangmarg proved to be substantially better for the growth of B. amplexicaulis, as per the Principal component analysis (PCA). The regression analysis demonstrated a negative relation between altitude and plant height. Traits such as leaf length/ breadth, Rhizome length/ breadth and inflorescence length showed a strong correlation with plant height. Our results provide an inclusive description of the phenotypic variability of this significant medicinal plant in response to the habitat variability across different altitudes.